Management of information technology projects - Schwalbe, Kathy (Singapore Cengage Learning, 2011)
"A comprehensive overview of the management of IT projects. Grounded in the latest research, it offers practical tools and techniques to help students at every stage of the project, from initial planning through to trouble-shooting specific problems. Ideal for undergraduate, graduate and MBA students taking a course in project management"--
Includes bibliographical references (p. 484) and index.
IT
Keywords: Information technology -- Management; Project management